Eating disorders among medical students of a rural teaching hospital: a cross-sectional study - Ramaiah, Radha R. (International Journal Of Community Medicine And Public Health, 2017)
Background:Eating disorders are complex psychiatric syndromes in that can lead to significant and potentially life threatening medical and nutrition complications. Literature from India in this regard is restricted and issues such as eating attitudes and body shape dissatisfaction remain unexplored in the Indian setting. It has been argued that eating disorders are culture-bound disorders specific to western societies. Consequently, these conditions remain understudied in most non-western settings. Objectives: 1) To determine the prevalence of eating disorders and body shape perception among medical students. 2) To assess any association between eating disorders and body shape perception. Methods:A cross-sectional study was conducted among 172 medical students using Eating Attitudes Test-26 (EAT-26), and the Body Shape Questionnaire (BSQ). Anthropometric measurements like height, weight was done for body mass index calculation and analysis was done with open Epi and Microsoft excel. Results:An overall prevalence of overweight was calculated to be 17.4% and obesity, 6.4%. The prevalence of eating disorder symptoms and disordered eating attitudes and behaviours in our study was 16.9% and a significant correlation between distorted eating attitudes and age with body shape dissatisfaction was found. Conclusions:The prevalence of overweight and obesity is on rise and a comparable level of eating disorders was observed. It is recommended to assess BMI along with the body shape concerns while screening for eating disorders among medical students.